A Comparative Study Of Ultrasonography And Magnetic Resonance Imaging In Detection And Analysis Of Ovarian Lesions - Rehbar, Nisha; Kumar, Ganesh; Sultana, Sadaf; Sharma, Shivam; Sheikh, Rashid (Journal of Neonatal Surgery, 2025)
Background: Ovarian lesions present an extensive spectrum of pathology, from benign cysts to malignant neoplasms, often posing diagnostic challenges, especially in resource-constrained settings. In India, ovarian cancer remains a major cause of gynecological morbidity and mortality, largely due to delayed diagnosis and limited access to advanced imaging modalities. Objective: This study aimed to compare the diagnostic accuracy of ultrasonography (USG) and magnetic resonance imaging (MRI) in detecting and characterizing ovarian lesions to determine their relative efficacy in differentiating benign from malignant pathology. Methodology: A prospective observational study was conducted over 18 months (May 2023–November 2024) at Lucknow. Forty-five female patients aged 17–60 years with clinically suspected ovarian lesions underwent USG and MRI. Imaging findings were evaluated independently by blinded radiologists, and diagnoses were confirmed by histopathology or intraoperative findings. Lesions were assessed based on morphological features, vascularity, and associated findings. Sensitivity, specificity, PPV, and NPV were calculated, and comparative diagnostic accuracy between USG and MRI was statistically analyzed. Results: Among the 45 cases, 36 (80%) were benign and 9 (20%) malignant. MRI demonstrated higher sensitivity and specificity in detecting malignant features such as solid components, papillary projections, ascites, and omental deposits, especially in complex and cystic lesions. While USG was effective in evaluating simple cysts and hemorrhagic lesions, it showed limitations in accurately classifying borderline and malignant lesions. Statistically significant differences were observed in diagnostic performance, favoring MRI over USG (p < 0.05). Conclusion: MRI demonstrated superior diagnostic accuracy over ultrasonography in evaluating ovarian lesions, particularly in distinguishing benign from malignant masses. Its enhanced sensitivity in detecting malignant features and better concordance with histopathology highlight its critical role in accurate, non-invasive preoperative assessment and management planning.